Pertumbuhan dan Produksi Tanaman Jagung (Zea mays L.) pada Beberapa Sistem Jajar Legowo dan Arah Tanam - Wahyu Wirawan; Haerul -; Nining Haerani (Program Studi Agroteknologi Fakultas Pertanian, Peternakan, dan Kehutanan Universitas Muslim Maros, 2023)
Low corn production will have an impact on domestic food and feed needs, this productivity can be increased through agricultural intensification, including the use of the jajar legowo cropping system and planting directions. This study used a factorial randomized block design (RBD) method consisting of 2 treatment factors, namely: 1). The spacing of legowo consists of 3 levels of treatment, namely: row legowo 2: 1, row legowo 3: 1 and row legowo 4: 1. 2). Planting direction with 2 treatment levels, namely: East-West planting direction and North-South planting direction. The results showed that the treatment of several jajar legowo cropping systems had no significant effect on the growth and production of maize plants. , and dry shell weight. The planting direction treatment had no significant effect on the growth and production of corn plants, the east-west planting direction gave the best results on cob length, cob weight, wet shell weight, and dry shell weight while the north-south planting direction gave the best results on plant height. number of leaves and stem diameter. and the combination of several jajar legowo cropping systems and planting directions had no significant effect on the growth and production of corn plants.